Eruptive history and magmatic stability of Erebus volcano, Antarctica: Insights from englacial tephra. (10th November 2014) - Iverson, Nels A.; Kyle, Philip R.; Dunbar, Nelia W.; McIntosh, William C.; Pearce, Nicholas J. G.
Abstract A tephrostratigraphy of the active Antarctic Erebus volcano was determined from englacial tephra on the ice‐covered flanks of Erebus and an adjacent volcano. The tephra are used to reconstruct the eruptive history and magmatic evolution of Erebus. More fine‐grained and blocky particles define tephra formed in phreatomagmatic eruptions and larger fluidal shards are characteristic of magmatic eruptions and in some cases both eruptive types are identified in a single mixed tephra. The eruptions forming the mixed tephra likely started as phreatomagmatic eruptions which transitioned into Strombolian eruptions as the nonmagmatic water source was exhausted. We reconstructed the eruptive history of Erebus using the tephra layers stratigraphic position, 40Ar/39Ar ages, shard morphology, and grain size. Major and trace element analyses of individual glass shards were measured by electron probe microanalysis and LA‐ICP‐MS. Trachybasalt, trachyte, and phonolite tephra were identified. All phonolitic tephra are Erebus‐derived with compositions similar to volcanic bombs erupted from Erebus over the past 40 years. The tephra show that Erebus magma has not significantly changed for 40 ka. The uniformity of the glass chemical composition implies that the phonolite magma has crystallized in the same manner without change throughout the late Quaternary, suggesting long‐term stability of the Erebus magmatic system. Trachyte and trachybasalt tephra were likely erupted from Marie Byrd Land and the McMurdo Sound area, respectively. The trachytic tephra can be regionally correlated and could provide an important time‐stratigraphic marker in Antarctic ice cores.